KNOWLEDGE AND AWARENESS ASSESSMENT OF MEDICAL STUDENTS TOWARDSBLS IN KSA. (CAHIERS MAGELLANES-NS, 2024)
Background: Cardiovascular disorders are the second most prevalent cause of death globally, behindauto accidents. The probability of survival in such circumstances is increased by prompt treatment, suchas Basic Life Support (BLS). Therefore, there is an urgent need for everyone to have sufficientawareness of emergency procedures like BLS, especially health care workers and students. To evaluatethe knowledge and awareness level of basic life support among medical students in KSA.Methods: This study was cross-sectional study, based on online questionnaire that allowed us toexamine the knowledge and awareness level of basic life support among medical students in SaudiArabia. The study population consisted of students studying in medical college in Kingdom SaudiArabia, participants were recruited during August 2023 to May 2024.Results: the total sample size were 732 participants. As regard knowledge score of medical studentstowards BLS in KSA, 21.2% demonstrated a high level of knowledge in BLS, while a majority of 55.9%fell within the medium knowledge level category. Additionally, 23.0% of students were classified ashaving a low level of knowledge in BLS. Moreover, awareness score of medical students towards BLSrevealed that 48.2%, fall under the High-Level category. Furthermore, 47.3% of respondentsdemonstrating a moderate level of awareness. However, it is worth noting that a small proportion ofrespondents, accounting for 4.5%, exhibit a low level of awareness towards BLS. Additionally, therewas a statistically significant relation between knowledge level and age (p value=0.002), academic year(p value=0.011) and GPA (p value=0.011). It also shows statistically insignificant relation to gender,nationality, and marital status.Conclusion: the study conducted among medical students in Saudi Arabia revealed varying levels ofknowledge and awareness regarding basic life support (BLS) with the majority having adequate levelof knowledge and awareness. A significant relationship was observed between knowledge level andfactors such as age, academic year, and GPA. Discrepancies in BLS education and preparedness werenoted in other studies across different regions, highlighting the importance of consistent andcomprehensive BLS training for medical students worldwide. Addressing these gaps in knowledge andskills can significantly enhance the ability of healthcare providers to respond effectively to emergenciesand improve patient outcomes